Preliminary Study of Postural Safety and Ergonomics Analysis Related to Cycling Activity - Mohd Azrin, Mohd Said; Khairunnisa, Zainuddin; Nor Kamaliana, Khamis (FAKULTI PERUBATAN DAN SAINS KESIHATAN, UPM SERDANG, 2022)
Introduction: In cycling activity, having a good proper posture can reflect good performance and comfort of the cyclist. Incorrect posture will lead to future health problems such as back pain. On some occasions, the muscle activity of the cyclist also can be affected due to improper posture, non-ergonomic posture. Design and load can be major factors of injury as well. This preliminary study helped to identify and investigate the postural safety and ergonomic analysis of cyclist muscle activity during cycling. Methods: A questionnaire was used to get an overview and prior knowledge of postural safety and ergonomic of random cyclists on the university campus. Then, Surface Electromyography sEMG and postural angle from Kinovea software were used to measure and compare the results with and without load among cyclists. In this study, there was a significant effect of saddle height and pedalling on the cyclist’s body posture. This showed an optimum power and effectiveness performance while cycling. This led to comfort and reduce the chance of injury such as back pain towards cyclist. Results: Based on the results, the lower back muscles activity pattern for cyclists with the load was higher compared to cyclists without the load (the optimum saddle height was applied). The cyclist’s lower back muscles activity showed an increasing pattern overtime. Conclusion: Therefore, this study will be helpful to the cyclist to get awareness regarding correct posture safety and feel more comfortable when cycling. Further improvement should be taken for future enhancement of the findings. Malaysian Journal of Medicine and Health Sciences (2022) 18(9):27-33. doi:10.47836/mjmhs18.s9.4